Artificial Intelligence And Education: Why, How And What - Judikis Preller, Juan Carlos; Quintana Albalat, Jordi (My University, 2024)
The present volume explores the broad impact of artificial intelligence in education by presenting a broad range of perspectives from some leading experts in the field. An initial chapter tackles macro level considerations from a social and anthropological perspective. Further, chapters explore more specific topics, ranging from philosophical aspects to the implications of AI in pedagogy and andragogy. The final chapter attempts to integrate the disparate aspects of the dialogue into a cohesive voice.